Geographic positioning as a determination of tourism development of Gevgelija region - Mijalce Gjorgievski; Sasko Gramatnikovski; Dejan Nakovski (UTMS Journal of Economics, 2013)
The research of this paper is about casinos in the southernmost city in the Republic of Macedonia - Gevgelija, its geographical position and their role on the development of gambling tourism. Gambling tourism as a special form of tourism, for some world famous tourist destinations is the main form of tourism. In some of them such as in Las Vegas and Monte Carlo, gambling tourism was the basic form of tourism, which further over time initiated rapid economic development of destinations and thanks exactly this kind of tourism they are today one of the most visited tourist destinations. Gevgelija with their casinos in a combination of other factors that influence the development of gambling tourism, especially geographical position, have excellent opportunities for its development, which today is in the initial phase and in the future, with the evolution of the tourist destination, Gevgelija can become known and desirable tourist destination. Today in Gevgelija a new business is born that citizens still do not know about, but day by day thoughts change, primarily because the large and rich countries had the capacity to develop this type of tourism, however we are not rich nor a large country. Today Gevgelija lives in the world of casinos.
Keywords: R12; R19; O18; 330; tourism; gambling; casinos; entertainment; games